TIPE2 suppresses ferroptosis and pro-inflammatory polarization in macrophages triggered by SARS-CoV-2 spike protein - Simin Zhu; Wei Li; Yuqiu Hao; Lin Zhang; Peng Gao (Scientific Reports)
Abstract As an acute respiratory infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), Coronavirus Disease 2019 (COVID-19) exhibits remarkable contagiousness and has emerged as a critical global public health concern. In critically ill patients, virus-induced cytokine storms and resulting multi-organ failure represent significant therapeutic challenges. In our clinical observations, we identified that this hyperinflammatory state was correlated with reduced mRNA expression of both Tumor Necrosis Factor-α-Induced Protein 8-like Protein 2 (TIPE2)—an immune negative modulator—and the ferroptosis marker gene Glutathione Peroxidase 4 (GPx4) in peripheral blood mononuclear cells (PBMCs) of these patients. Given the emerging evidence that macrophage polarization and dysfunction play pivotal roles in COVID-19 progression, we established a THP-1-derived macrophage model stimulated with the SARS-CoV-2 spike (S) protein to mimic the host immune response. Our results demonstrated that TIPE2 modulates S protein-induced macrophage polarization and ferroptosis, specifically by suppressing M1 polarization associated with inflammation and encouraging M2 polarization linked to anti-inflammatory responses, thereby alleviating inflammatory responses. These findings suggest that TIPE2 mediates critical immunomodulatory effects during the progression of SARS-CoV-2 infection, positioning it as a promising therapeutic target for mitigating pathological inflammatory responses in COVID-19 patients gravely affected.